Pengaruh Kepemimpinan Kepala Sekolah, Motivasi Kerja Guru Dan Budaya Sekolah Terhadap Kedisiplinan Siswa Di Kabupaten Polewali Mandar - Muhammad Syaeba (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2017)
This study aims to reveal the contribution of principals‟leadership, teach-ers‟ work motivation, and school culture on the discipline of senior high school students and vocational high school students in Polewali Mandar, Sulawesi Barat. This study was an expost facto study. The research subjects consisted of all 425 senior high school teachers in Polewali Mandar Regency, Sulawesi Barat and a sample of 193 was established using the proportionate cluster random sampling technique. The data were collected by means of a questionnaire and analyzed using the multiple regression technique to test the research hypotheses. The results of this study show that there is positive and significant contribution of: (1)the principals‟ transformational leadership on the discipline of the students as much as 39.8%; (2) the teachers‟ work motivation on the students‟ discipline as much as 20,7%; (3) the school culture on the discipline of the students as much as 38%; (4) principals‟ leadership, teachers‟ work motivation, and school culture as an aggregate on the students‟ discipline much as 52.6%. This indicates that if principals‟leadership, teachers‟ work motivation, and school culture are enhanced in quality, they will have positive contributions to senior high school teachers and vocational high school teachers in Polewali Mandar, Sulawesi Barat.